2011
DOI: 10.1248/yakushi.131.1843
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of 5-Lipoxygenase Increases the Neuronal Vulnerability of PC12 Cells to Aβ<sub>42</sub>

Abstract: 5-Lipoxygenase (5-LOX), which is believed to be a major source of oxidative stress, participates in somatostatinreceptor transmembrane signaling in the central nervous system. We used the Tet-On inducible expression system in PC12 cells to obtain cell lines with reproducible, stable 5-LOX expression levels to study its function. Cell apoptosis rates induced by Ab 42 were determined using an apo-BrdDU kit. Lipid peroxide, antioxidant enzyme, and caspase-3 activities were evaluated with respective commercial kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Oligomeric and fibrillar Aβ-42 also induces mitochondrial dysfunctions in cortical neurons, including a reduction in mitochondrial membrane potential, state 3 respiration, respiratory control ratio and uncoupled respiration ( 38 ). Consistent with a previous study ( 39 ), the present study demonstrated that Aβ-42 induced significant neuronal apoptosis, and activated the Caspase pathway. Ca 2+ is an active second messenger, and is involved in many cellular processes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Oligomeric and fibrillar Aβ-42 also induces mitochondrial dysfunctions in cortical neurons, including a reduction in mitochondrial membrane potential, state 3 respiration, respiratory control ratio and uncoupled respiration ( 38 ). Consistent with a previous study ( 39 ), the present study demonstrated that Aβ-42 induced significant neuronal apoptosis, and activated the Caspase pathway. Ca 2+ is an active second messenger, and is involved in many cellular processes.…”
Section: Discussionsupporting
confidence: 93%
“…In conclusion, the present study demonstrated that Aβ-42 treatment activated the Caspase signaling pathway, and induced obvious neuronal apoptosis. Although the role of Aβ-42 in neuronal survival has been described ( 14 , 39 ), to the best of our knowledge, these data demonstrated for the first time that Aβ-42 increases mitochondrial fission by changing the expression of mitochondrial fission and fusion proteins. Inhibition of Drp1-dependent mitochondrial fission efficiently suppressed Aβ-42-induced intracellular ROS production and loss of mitochondrial membrane potential in neurons.…”
Section: Discussionmentioning
confidence: 60%
“…Previous reports found that 5-LOX expression in the brain increases during aging (Chinnici et al, 2007; Uz et al, 1998) and in Alzheimer’s disease (Firuzi et al, 2008; Ikonomovic et al, 2008; Wang et al, 2011), but the aging-affected methylation status of the mouse 5-LOX gene has not been consistently related with the rate of 5-LOX transcription (Dzitoyeva et al, 2009). It has been noticed that global 5hmC changes do not necessary reflect the same type of 5hmC changes in individual gene sequences.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, ApoEˉ/ˉ mice lacking 5LO have reduced caspase-3 activity23, while overexpression of 5LO significantly enhanced caspase-3 activation in PC12 cells24, and 5LO pharmacological inhibition significantly down-regulated caspase-3 activation in the brains of rats undergoing middle cerebral artery occlusion25.…”
Section: Discussionmentioning
confidence: 99%